Ammonia and Hydrazine from Coordinated Dinitrogen by Complexes of Iron(0). Issue 14 (1st March 2019) - Field, Leslie D.; Li, Hsiu L.; Dalgarno, Scott J.; McIntosh, Ruaraidh D.
Abstract : The iron(0) dinitrogen complexes [Fe(N2 )(PP3 R )] (PP3 R = P(CH2 CH2 PR2 )3, R = Ph, i Pr, Cy) were synthesized by reduction of the precursor chloro complexes with potassium graphite. On reaction with triflic acid, [Fe(N2 )(PP3 R )] complexes afforded ammonia and hydrazine in yields of up to 23 and 16 % respectively. The complex [Fe(N2 )(PP3 Ph )] which has only been previously synthesized in situ, has now been isolated and fully characterized by 15 N NMR spectroscopy and by X‐ray crystallography. Abstract : In the presence of strong acids, coordinated N2 in [Fe(N2 )(PP3 R )] (PP3 R = P(CH2 CH2 PR2 )3 ; R = Ph, i Pr, Cy) is reduced to a mixture of ammonia and hydrazine. The bulky PP3 ligands were designed to partially encapsulate the metal center and to slow or inhibit the competing reaction of the metal center with acid.